Panthéisme de Flaubert - Philippe Dufour (Flaubert: Revue Critique et Génétique)
During the Romantic period in Europe, the great god Pan was back, in response to Christianity. The century read Spinoza, and Hegel analyzed pantheism, whereas the Abbé Maret fought against it. The young Flaubert participated in his fashion to the controversy, by his naturalist, sensitive pantheist, mysticism. But these euphoric moments in the midst of landscapes were counteracted by a feeling of melancholic loss of images which marked the rest of his work.